Mathuiz-B Android-Based Application Program to Overcome Dissimilarity in Mathematics Fields of Sabilurrosyad Islamic Junior High School Students - Pusawidjayanti, Kridha (Journal of Saintech Transfer, 2024)
Â  Sabilurrosyad Islamic Middle School is a junior high school in the village of Karangbesuki. The geography school is located on the edge of Malang City and far away from the center of Malang City. Students entering junior high school are big children from local public elementary school graduates. Sabilurrosyad Islamic Middle School is the school that found its students with diverse ability different academics. _ Problems faced _ partner is different competence academic field mathematics in students new Sabilurrosyad Islamic Middle School. Based on the results analysis situation and SWOT analysis, the team devoted the public to the solution by creating and giving application edugames (MATHUIZ-B) that can used by schools. For participants assigned to educate new order capabilities, cognitive students can be uniform with standard junior high school level. The method of this community activity begins with preparation, making the Mathuiz-B application, outreach to teachers and principals of Sabilurrosyad Middle School, and Submission of the application so that service partners can use it. On activities devotion public, team devotion will provide an application manual book and a book regarding successful strategies for learning mathematics for entering junior high school.